2015
DOI: 10.1016/j.bmc.2015.06.034
|View full text |Cite
|
Sign up to set email alerts
|

The twin drug approach for novel nicotinic acetylcholine receptor ligands

Abstract: The association of two pharmacophoric entities generates so-called “twin drugs” or dimer derivatives. We applied this approach for the design of a small compound library for the interaction with α4β2* nicotinic acetylcholine receptors (nAChRs). In this compound series, the nAChR ligand N,N-dimethyl-2-(pyridin-3-yloxy)ethan-1-amine 9 served as one pharmacological entity and it was initially kept constant as one part of the “twin” compound. “Twin” compounds with identical or non-identical entities using the “no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Tomassoli and Gündisch were able to couple 3-bromopyridine 84 and (di)aza(bi)cyclic species 85 in the presence of an L6 -based catalyst ( Scheme 13 b). 93 A solvent mixture composed of toluene and t- BuOH was required to promote solubility of the coupling partners, and microwave heating enhanced C–N bond formation. Prior protection of one nitrogen atom in 85 was necessary to prevent diarylation.…”
Section: Alkylaminesmentioning
confidence: 99%
“…Tomassoli and Gündisch were able to couple 3-bromopyridine 84 and (di)aza(bi)cyclic species 85 in the presence of an L6 -based catalyst ( Scheme 13 b). 93 A solvent mixture composed of toluene and t- BuOH was required to promote solubility of the coupling partners, and microwave heating enhanced C–N bond formation. Prior protection of one nitrogen atom in 85 was necessary to prevent diarylation.…”
Section: Alkylaminesmentioning
confidence: 99%
“…According to specific needs and applications, the NCNDs can be modified by postfunctionalization reactions. Herein we report two different reactions that exemplify the surface amine modifications of the NCNDs (A) carbodiimide coupling with molecules bearing carboxylic groups and (B) reductive methylation (Eschweiler-Clarke reaction) 48,49 . Leave the solution to warm-up gradually to r.t. and let it stir overnight, under Ar.…”
Section: Part 2: Post-functionalization and Purification Of Cnds • Timentioning
confidence: 99%
“…In the medicinal chemistry research field Pd(OAc) 2 catalysed coupling reactions in Q-tube were recently reported [26,27]. In one example, the use of such system was required, as the author stated, to reduce the reaction time [27].…”
Section: Catalytic Approachesmentioning
confidence: 99%
“…The hydrodeoxygenation of condensates (26)(27)(28) was accomplished in the liquid phase at 160 °C with 3. catalyst, react. cond.…”
Section: Biofuels Developmentmentioning
confidence: 99%